2022
DOI: 10.1111/jdv.18183
|View full text |Cite
|
Sign up to set email alerts
|

Chlormethine gel is effective for the treatment of skin lesions in patients with early‐ and late‐stage mycosis fungoides in clinical practice

Abstract: Background Chlormethine gel is a skin-directed therapy used for patients with mycosis fungoides (MF) that showed a favourable risk/benefit profile in a randomized clinical trial. Currently, data on chlormethine gel use in real-world settings are limited.Objectives The aim of this study was to assess safety and efficacy of chlormethine gel treatment in patients treated during daily clinical practice and investigate associations between response and disease stage, lesion type, mono-or combination therapy, and oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…In a retrospective evaluation of 18 patients, only 1 was treatment-naïve when initiating chlormethine gel, with 7 patients having received 2–4 prior lines of therapy and 8 patients having had more than 5 prior therapies ( 7 ). Another retrospective study included 58 patients who all received prior therapies, including prior phototherapy or bexarotene, and had good responses to chlormethine gel treatment ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective evaluation of 18 patients, only 1 was treatment-naïve when initiating chlormethine gel, with 7 patients having received 2–4 prior lines of therapy and 8 patients having had more than 5 prior therapies ( 7 ). Another retrospective study included 58 patients who all received prior therapies, including prior phototherapy or bexarotene, and had good responses to chlormethine gel treatment ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“… Development of contact dermatitis associated with CAILs response (p = 0.0001). Papadavid et al (2022) 15 Retrospective analysis N = 58 Stage IA–IIB NM 0.02% gel monotherapy or combination therapy ORR assessed as ≥ 50% improvement in mSWAT scores. Quality-of-life assessments via Skindex-29.…”
Section: Efficacy Of Topical Nmmentioning
confidence: 99%
“…9 In a 2022 study of 58 patients based out of Greece, gel-based NM was also found to be safe and effective in a real-world setting; however, 72.4% experienced some form of skin irritation. 15 …”
Section: Adverse Effects Of Topical Nmmentioning
confidence: 99%
See 2 more Smart Citations